MICROBIAL ACTIVITY AND PERFORMANCE OF AN ANAEROBIC REACTOR COMBINING A FILTER AND A SLUDGE BED - CHUNG, YC; CHOI, YS (PERGAMON-ELSEVIER SCIENCE LTD, 1993)
Microbial activity and performance of anaerobic upflow sludge bed filter(AUBF) were investigated using two types of AUBF: 1/2 packed (AUBF-1/2) and 1/7 packed (AUBF-1/7) with media, and a fully packed anaerobic filter (AF). Each reactor was loaded with 1 to 3 kg COD/m3-day of distillery wastewater using naked barley as raw material. Adenosine triphosphate and dehydrogenase activity measurements were applied to measure the microbial activity in the reactors. AUBF presented comparable treatment efficiencies, while the microbial activity in AUBF is equal to or higher than in AF. Upper packing and lower sludge bed were very efficient to retain the biomass and reduce the amount of packings needed without sacrificing the performance. However, AUBF resulted in less process stability at shock loading than AF, and operation of AUBF needs more careful control to maintain the stability.